(untitled) (Journal of Student Affairs in Africa, 2021)
Lack of sufficient accommodation in many South African universities has forced many students to reside outside the campus and commute to attend classes as commuter students. Research indicates that living on campus is related to gains in social and personal competence. The level of competence gained may help students living on campus (resident students) to be more successful in their courses. The purpose of this study was to compare the academic performance of resident and non-resident students at a university in Limpopo Province. The study employed a survey design. Systematic sampling and snowball sampling methods were used to select 1 769 participants from both resident and non-resident students. A questionnaire was used to collect data. The main finding from this study is that the academic performance of resident students is slightly better than that of non-resident students - hence, residing on campus is an advantage. The study concludes that campus environment, student involvement as well as student academic and social integration into the institution tend to account for effects of living on-campus versus living off-campus. Furthermore, academic and social integration of students at university are essential for study commitment, success and preventing students from dropping out. The study recommends that future research should focus on the direct influence of resident versus commuterstatus on such outcomes as degree aspiration, satisfaction with university and institutional persistence.